2019
DOI: 10.1088/1742-5468/ab3191
|View full text |Cite
|
Sign up to set email alerts
|

Analytical results for the in-degree and out-degree distributions of directed random networks that grow by node duplication

Abstract: We present exact analytical results for the degree distribution in a directed network model that grows by node duplication (ND). Such models are useful in the study of the structure and growth dynamics of gene regulatory networks and scientific citation networks. Starting from an initial seed network, at each time step a random node, referred to as a mother node, is selected for duplication. Its daughter node is added to the network and duplicates each outgoing link of the mother node with probability p . In a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…However, apart from a few studies [26,[61][62][63][64][65][66] the DSPL has not attracted nearly as much attention as the degree distribution. Recently, an analytical approach was developed for calculating the DSPL in the (ER) network [67], followed by more general formulations that apply to configuration model networks [43,68,69], to modular networks [70] and to networks that form by kinetic growth processes [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, apart from a few studies [26,[61][62][63][64][65][66] the DSPL has not attracted nearly as much attention as the degree distribution. Recently, an analytical approach was developed for calculating the DSPL in the (ER) network [67], followed by more general formulations that apply to configuration model networks [43,68,69], to modular networks [70] and to networks that form by kinetic growth processes [71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…8(b) we present the probability P (e ∈ B) that a random edge in a configuration model network with an exponential degree distribution is a bredge (solid line), as a function of c, obtained from Eq. (73). We also present the probability P (e ∈ B, GC) (dashed line) that a randomly selected edge in the network is a bredge that resides in the giant component and the probability P (e ∈ B, FC) (dotted line) that a randomly selected edge in the network is a bredge that resides in one of the finite components.…”
Section: B Configuration Model Network With Exponential Degree Distri...mentioning
confidence: 99%
“…In this model, nodes are more likely to connect to nodes that already have a large number of knowledge connections, referred to by Price as the 'cumulative advantage effect' 2 also known as, in the context of un-directed links, 'preferential attachment' [7]. In many applications of the Price model, the focus is on degree distributions, which describe how outgoing or incoming links are distributed over nodes [7,41,35]. While these distributions to an important extent determine network structures, they are mainly revealing for the variation in the relative importance of nodes, and perhaps less useful to study to what extent there is knowledge flow in such networks.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent paper we introduced a directed version of the corded node duplication network model and studied its in-degree and out-degree distributions [66]. This model is referred to as the corded directed node duplication (DND) model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the degree distribution consists of two separate distributions, namely the distribution P t (K in = k) of in-degrees and the distribution P t (K out = k) of out-degrees, at time t. These two distributions are related to each other by the constraint that their means must be equal, namely K in t = K out t . We obtained exact analytical results for the in-degree distribution and the out-degree distribution of the corded DND network [66]. It was found that the in-degrees follow a shifted power-law distribution while the out-degrees follow a narrow distribution that converges to a Poisson distribution in the sparse network limit and to a Gaussian distribution in the dense network limit.…”
Section: Introductionmentioning
confidence: 99%